The housing question : ideology, access or action? : an examination of housing provision in New Zealand : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Geography at Massey University - Salmon, Scott (Massey University, 1987)
The inspiration for investigating this topic, and the material for the case examples, grew out of a period between 1981 and 1986 during which time I became heavily involved in dealing with the consequences of various aspects of Palmerston North's housing shortage. I was, at that time employed as Co-ordinator of Community Volunteers (P.N.) Inc., a small non-profit urban based community work agency. In the course of my work I was involved with the problem on several fronts; dealing with those directly affected by the shortage; the homeless, secondly: trying to raise awareness of the problem amongst those who held power and controlled resources in the city, attempting to persuade them to take some positive action to increase the housing stock. While much of my work at Community Volunteers was, of necessity, related to dealing with the immediate issues it was this experience that made me aware of the complex and interconnected nature of the city's problems. Taking time out to complete this thesis has allowed me the luxury of standing back from the exigencies of my previous position to investigate the deeper ongoing processes and to gain an overview of the urban scene. I felt strongly that it was important not just to indulge in "moral masturbation" by compiling some 'huge dossier on the daily injustices to the populace' (Harvey 1973:145) but to identify and explain the processes that have led to and perpetuate the particular housing problems that Palmerston North is experiencing in such a way that the knowledge gained can be applied to the task of bringing about a humanizing social change.
Keywords: Housing, New Zealand; Housing policy, New Zealand; Palmerston North; Housing shortage